2017
DOI: 10.20546/ijcrar.2017.511.003
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Lactic Acid Bacteria against Toxigenic Fungi

Abstract: Article InfoLactobacillus bulgaricus S 2 was widely used in fermentation and preservation of food and it was assayed on their fungal inhibitory properties. The aim of this study was to isolate lactic acid bacteria from different habitats and screen these isolates against some mycotoxigenic fungi. The effect of lactic acid bacteria (LAB) on growth of a mycotoxin-producing toxigenic fungi was assayed. Assays were carried out by modified overlay method. Lactobacillus bulgaricus S 2 assays showed growth inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The present study revealed that most of local and imported wheat grains samples were contaminated with the common genus of fungi: Aspergillus, Penicillium, Fusarium, Alternaria and Cladosporium. Indeed, several sci- entific investigations in cereal fungal contamination were revealed around the world and demonstrated that this contamination was caused especially by the cited genus and the results obtained were in agreement with the previous findings (Ferreira-Geraldo et al, 2006;Pitt and Hocking, 2009;Chehri et al, 2010;Franco et al, 2011;Battilani et al, 2016;Nagaraja et al, 2016;Al-Haik et al, 2017;Djaaboub et al, 2018). According to Klich (2002) fungus propagules get on grain most often with dust from soil, from the surface of plant remnants.…”
Section: Discussionsupporting
confidence: 85%
“…The present study revealed that most of local and imported wheat grains samples were contaminated with the common genus of fungi: Aspergillus, Penicillium, Fusarium, Alternaria and Cladosporium. Indeed, several sci- entific investigations in cereal fungal contamination were revealed around the world and demonstrated that this contamination was caused especially by the cited genus and the results obtained were in agreement with the previous findings (Ferreira-Geraldo et al, 2006;Pitt and Hocking, 2009;Chehri et al, 2010;Franco et al, 2011;Battilani et al, 2016;Nagaraja et al, 2016;Al-Haik et al, 2017;Djaaboub et al, 2018). According to Klich (2002) fungus propagules get on grain most often with dust from soil, from the surface of plant remnants.…”
Section: Discussionsupporting
confidence: 85%
“…Other authors confirmed that L. acidophilus exerts biostatic effect on the fungal growth due to the accumulation of organic acids (Denkova et al, 2013). L. acidophilus strain is able to detoxify the mycotoxins (Al-Haik et al, 2017).…”
Section: S: Spoiled Samplementioning
confidence: 99%
“…In modern society, there is increasing demand for safe, healthy foods with high quality and preservatives-free products (Keenan et al, 2011 andDinev et al, 2017). In this context, biopreservation, by using beneficial microorganisms and/or their metabolites to prevent spoilage, extend the shelf-life of foods with excellent technological properties without chemical preservatives, has attracted consumer interest (Wang et al, 2012 andAl-Haik et al, 2017).…”
Section: Introductionmentioning
confidence: 99%